Tiga Tahap Formulasi Strategi Pembangunan Sektor Pertanian di Kabupaten Lebak - Adi Prasetya Muammar; Iwan Setiawan; Zumi Saidah (Politeknik Negeri Lampung., 2022)
The agricultural sector development strategy should be based on a comprehensive identification of various problems and the involvement of various interest groups. This study aims to produce priority alternative strategies for the government in Lebak Regency. The research method used in this study was a research based on qualitative and quantitative data. Data collection method used in qualitative data was interviews and quantitative data was questionnaires. The source of information that was being searched was Lebak regency government, farmer, agricultural expert, and strategic management expert. From the data collected, it was sorted according to the stages and then analyzed using SWOT and QSPM analysis. The results of the study show that first, several internal and external factors were identified from the interviews, second, the strategic position of the Lebak Regency government in agricultural development efforts was grow and build position, and third, there were nine alternative priority strategies for the development of the agricultural sector. The strategy that becomes the main alternative is “Be active in collecting information on assistance or cooperation programs from the central, provincial, regional government or other institutions”. This strategy is the first priority ranking that needs to be considered in the local government policy of the Lebak Regency.